2019
DOI: 10.1111/iju.13965
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, type and management of ureteric injury associated with vesicovaginal fistulas: Report of a series from a specialized center

Abstract: Objectives To report a large series of vesicovaginal fistula, and to assess the incidence of ureteric injury in association with vesicovaginal fistula. Methods We retrospectively reviewed a prospective database of patients with vesicovaginal fistula referred to our center between 2004 and 2016. Data on patient demographics, fistula etiology, mode of repair, and any associated ureteric injury and its treatment were noted. Results Overall, 116 patients (median age 49 years, range 23–88 years) were referred for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…3 However, preoperative diagnosis is essential for the planning of repair surgery. The article by Seth et al 4 presents a large series of 116 patients with VVF, emphasizing the incidence and management of these patients when there is an association of ureteral injury. These authors found just four cases of VVF with concomitant ureteral injury (3.4%), which is a significantly low incidence.…”
Section: Editorial Commentmentioning
confidence: 99%
“…3 However, preoperative diagnosis is essential for the planning of repair surgery. The article by Seth et al 4 presents a large series of 116 patients with VVF, emphasizing the incidence and management of these patients when there is an association of ureteral injury. These authors found just four cases of VVF with concomitant ureteral injury (3.4%), which is a significantly low incidence.…”
Section: Editorial Commentmentioning
confidence: 99%